2012
DOI: 10.1007/s10709-012-9695-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of the Appenine endemic cyprinid fish Squalius lucumonis and three other Italian leuciscines using chromosome banding and FISH with rDNA probes

Abstract: Karyotype and other chromosomal characteristics of the Appenine endemic cyprinid fish, Toscana stream chub Squalius lucumonis, were analysed using conventional banding and FISH with 45S and 5S rDNA probes. The diploid chromosome number (2n = 50) and karyotype characteristics including pericentromeric heterochromatic blocks and GC-rich CMA(3)-positive sites corresponding to both positive Ag-NORs and 45S rDNA loci on the short arms of a single medium-sized submetacentric chromosome pair were consistent with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Species-specific rDNA polymorphisms were recently characterized in European leuciscines (Gromicho et al, 2006a,b;Kirtiklis et al, 2010;Pereira et al, 2012;Rossi et al, 2012), as well as in artificially reared hybrids of the Squalius alburnoides complex (Gromicho et al, 2006b). In the present study, each hybrid stood for a distinct rDNA profile, usually falling within the range of possible combinations of parental contributions (Supplementary Table S3) and reflecting their admixed nature.…”
Section: Hybrid Rdna Polymorphisms-genetic Noveltiesmentioning
confidence: 49%
See 1 more Smart Citation
“…Species-specific rDNA polymorphisms were recently characterized in European leuciscines (Gromicho et al, 2006a,b;Kirtiklis et al, 2010;Pereira et al, 2012;Rossi et al, 2012), as well as in artificially reared hybrids of the Squalius alburnoides complex (Gromicho et al, 2006b). In the present study, each hybrid stood for a distinct rDNA profile, usually falling within the range of possible combinations of parental contributions (Supplementary Table S3) and reflecting their admixed nature.…”
Section: Hybrid Rdna Polymorphisms-genetic Noveltiesmentioning
confidence: 49%
“…The number of studies in cyprinids using dual-FISH with rDNA probes is frankly growing, and colocalized ribosomal genes in leuciscines were described within Anaecypris, Leuciscus and Squalius genera (Gromicho et al, 2006a,b;Kirtiklis et al, 2010;Rossi et al, 2012) but never in chondrostomine species (for example, parental species under focus; Pereira et al, 2012). The novel syntenic associations (Figures 2-4) are distinct evidences of genome instability and reshuffling, most likely driven by the hybridization events (Fontdevila, 2005;Abbott et al, 2013).…”
Section: Hybrid Rdna Polymorphisms-genetic Noveltiesmentioning
confidence: 99%
“…the large subtelo-to acrocentric, 1 large metacentric, 1-2 large submetacentric and NOR-bearing chromosome pairs); (2) confirm the polymorphism of NORs in several Iberian [Collares- Pereira and Ráb, 1999;Gromicho et al, 2005Gromicho et al, , 2006aPereira et al, 2009Pereira et al, , 2012 and non-Iberian leuciscine species [e.g. Bóron et al, 2009;Kirtiklis et al, 2010;Rossi et al, 2012], suggestive of multiple independent origins for the translocation and/or multiplication of rDNA clusters within each lineage; and (3) successfully distinguish species and their hybrids [e.g. Kirtiklis et al, 2010;Pereira et al, in press].…”
Section: Molecular Cytogeneticsmentioning
confidence: 79%
“…The first case of European leuciscines with multiple NORs was confirmed by FISH with a specific probe for major ribosomal RNA genes (rDNA) [Collares-Pereira and Ráb, 1999], opposing the apparently widely distributed condition of a single pair of NORs on a medium-sized submetacentric chromosome pair. Regarding the minor rDNA clusters, recent studies suggested the large subtelo-to acrocentric chromosome pair as the ancestral 5S-rDNAbearing chromosome for the entire Leuciscinae, despite revealing greater variation in number and location than 45S rDNA clusters Rossi et al, 2012]. Simultaneous mapping of both minor (5S) and major (45S = 18S + 5.8S + 28S) rDNA families by dual-color FISH provided further advances regarding genome organization in these species.…”
Section: Molecular Cytogeneticsmentioning
confidence: 99%
See 1 more Smart Citation